1996
DOI: 10.1111/j.1365-2095.1996.tb00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cholesterol additions to a soyabean meal-based diet for juvenile Pacific white shrimp, Penaeus vannamei (Boone), in an outdoor growth trial

Abstract: Cholesterol is considered a required nutrient for penaeid shrimps, but an optimal level has not been defined. A 68-day grow-out trial was conducted in 1300-L outdoor tanks in Hawaii, USA, to determine the cholesterol level required in a soyabean meal-based diet for juvenile Pacific white shrimp, Penaeus vannamei (Boone).Test feeds were prepared by adding six cholesterol levels (1.0-10.2 g kg-', as-fed basis) to a standard diet high in plantprotein meals, starch and flour. These feeds were provided to the shrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…The cholesterol content of the OI diet, by contrast, was kept low by eliminating cholesterol-containing ingredients. Indeed, the level of cholesterol in the OI diet was lower than the level (0.23%) reported by Duerr and Walsh (1996) to maximize shrimp productivity. The high growth and survival of the animals fed the very low cholesterol OI diet, which was equivalent to the growth and survival of shrimp maintained on the commercial control feeds in both trials, indicates that shrimp fed the OI diet were still able to satisfy their cholesterol requirement.…”
Section: Discussionmentioning
confidence: 61%
“…The cholesterol content of the OI diet, by contrast, was kept low by eliminating cholesterol-containing ingredients. Indeed, the level of cholesterol in the OI diet was lower than the level (0.23%) reported by Duerr and Walsh (1996) to maximize shrimp productivity. The high growth and survival of the animals fed the very low cholesterol OI diet, which was equivalent to the growth and survival of shrimp maintained on the commercial control feeds in both trials, indicates that shrimp fed the OI diet were still able to satisfy their cholesterol requirement.…”
Section: Discussionmentioning
confidence: 61%
“…() found that crayfish Pacifastacus leniusculus fed with sterol‐free diets exhibited the mortality syndrome characterized by incomplete ecdysis. Duerr & Walsh () found an increase in growth and survival in P. vannamei fed diets supplemented with cholesterol. As a kind of sterols, cholesterol was supplemented in juvenile E. sinensis diets to delineate effects of cholesterol on the moulting performances, further to study the moulting underlying preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the above immunological responses in haemocytes, cholesterol supplementation seems to be more helpful in enhancing cellular immunity for L. vannamei , compared with the other two feed additives. Published reports for L. vannamei of different age fed different diets under a variety of culture conditions showed cholesterol requirements are 0.14–0.68% (Duerr & Walsh ; Gong, Lawrence, Jiang, Castille & Gatlin ; Gong, Jiang, Lightner, Collins & Brock ; Wang ). In this study, cholesterol level in control diet was 1.00%, seemed not likely to be low in cholesterol for L. vannamei .…”
Section: Discussionmentioning
confidence: 99%